الاجهاد المهني وتأثيره على العلاقات الاجتماعية خارج نطاق العمل (Comprehensive Journal of Science, 2025)
This study aims to examine the impact of occupational stress on social relationships outside the workplace, focusing on the role of social support in alleviating such pressures. The descriptive-analytical approach was adopted, and data were collected from a stratified random sample of (50) participants working in various sectors, using a questionnaire consisting of three main dimensions: occupational stress, social relationships, and social support. The findings revealed a significant relationship between high levels of occupational stress and the deterioration of social relationship quality, while social support plays a positive role in mitigating the negative effects of stress. The study concludes with the importance of adopting work organization strategies and enhancing social support both inside and outside the workplace to improve professional and personal quality of life.Keywords: Occupational stress, Social relationships, Social support, Quality of life, Work stress.